2014
DOI: 10.1302/0301-620x.96b10.33771
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical footprint of the Achilles tendon

Abstract: We dissected 12 fresh-frozen leg specimens to identify the insertional footprint of each fascicle of the Achilles tendon on the calcaneum in relation to their corresponding muscles. A further ten embalmed specimens were examined to confirm an observation on the retrocalcaneal bursa. The superficial part of the insertion of the Achilles tendon is represented by fascicles from the medial head of the gastrocnemius muscle, which is inserted over the entire width of the inferior facet of the calcaneal tuberosity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 12 publications
4
68
4
Order By: Relevance
“…The latter is composed of two heads-the lateral head of gastrocnemius muscle (GL) and the medial head of gastrocnemius muscle (GM), from each of which originates an independent subtendon. [1][2][3][4][5][6][7][8] In 65% of the population, the plantaris tendon also contributes to the AT. 8 Proximally, the AT fibers join the triceps surae's muscle fibers at the level of musculo-tendinous junction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter is composed of two heads-the lateral head of gastrocnemius muscle (GL) and the medial head of gastrocnemius muscle (GM), from each of which originates an independent subtendon. [1][2][3][4][5][6][7][8] In 65% of the population, the plantaris tendon also contributes to the AT. 8 Proximally, the AT fibers join the triceps surae's muscle fibers at the level of musculo-tendinous junction.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]7,9 The AT inserts distally into the superior, middle, and inferior facets of the calcaneal tuberosity, and the width of its insertion varies from 20 to 48 mm. 1,[10][11][12][13] The twisted descending structure of the AT enables it to handle the functional loads applied to the tendon. The differences in the degree of torsion may in turn contribute to mechanisms of AT injury or may in part explain increased susceptibility to AT injury in certain individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the lateral head of the gastrocnemius, the medial head is wider, thicker and tighter, and with less complicated and variable neurovascular structures nearby [18,21]. A recent anatomic study revealed that the superficial part of the Achilles tendon is mainly from the medial head of the gastrocnemius and has continuity with the plantar fascia [22]. Only releasing the medial head may safely achieve a relatively satisfactory correction of the contracture [10,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…After excision the calcified and the inflamed tendon, a suture anchor was used to reattach and repair the Achilles tendon [15]. However, the results of this operation were not always satisfactory.…”
Section: Introductionmentioning
confidence: 99%